CONCEPT OF ELECTRON SOURCE BASED ON PULSED PLASMA DISCHARGE - Widdi Usada; Wirjoadi Wirjoadi; Agus Purwadi; Bambang Siswanto (Website, 2009)
CONCEPT OF ELECTRON SOURCE BASED ON PULSED PLASMA DISCHARGE. The lack of continuous electronbeam machine is electron current limitation and heating impact on target. So it is needed a new machine which will givehigher current in the pulsed mode operation. This paper offers on the possibility of pulsed plasma discharge as a pulseelectron source. By using simple equation, it can be achieved some interesting parameters such as plasma current,rise time etc. The result is useful as basic understanding in designing this machine.